Altitudinal Variation of the Numerical Structure and Biodiversity of the Taxocenosis of Ephemeroptera in the South, North, and Central Regions of the Department of Antioquia, Colombia. (2004)
ABSTRACT: Aiming at the study of the altitudinal variation of the numerical structure and biodiversity of the taxocenosis of Ephemeroptera, samples were taken between June and December, 1998 in 35 streams located in three life zones in the Department of Antioquia. Seven families, 22 taxa and 19 genera were found, out of which Bernerius, Cloeodes, Mayobaetis, Atopophlebia, Farrodes, Haplohyphes, and Homothraulus are first records for Antioquia. Bernerius, Mayobaetis and Homothraulus genera are first cited for Colombian bentic fauna. The community found in the Premontane altitudinal zone was different to the rest. Similarity among zones was high; exchange among zones was moderate as shown by the reciprocal value of beta diversity with the two indexes used (DBW = 62%, DBR = 68%). The diversity of the Ephemeroptera community found in each zone was relatively high.